Sustainable and cost-efficient energy supply and utilisation through innovative concepts and technologies at regional, urban and single-user scales. (1st September 2019) - Piacentino, Antonio; Duic, Neven; Markovska, Natasa; Mathiesen, Brian Vad; Guzović, Zvonimir; Eveloy, Valerie; Lund, Henrik
Abstract: The environmental impact of the energy sector and the security and economics of energy supply and utilisation have been raising increasing concerns, stimulating the search for innovative solutions for a sustainable use of resources. This article provides an overview of published research in this area, with a focus on papers contributed in special issues of leading journals dedicated to the series of Conferences on Sustainable Development of Energy, Water and Environment Systems (SDEWES), including the articles in the current special issue. Based on this review, research trends are identified and achievements supporting the energy transition are highlighted. The studies that focused on regional or urban energy planning have aimed at (a) increasing penetration of renewable energy sources, (b) optimizing the mix of centralized and distributed technologies (c) introducing additional flexibility in the power sector and (d) identifying solutions for sustainable heating. Conversely, researches focused on single plants or users have targeted the development of technologies for efficient energy use in industry and buildings, with emphasis on multi-generation and waste heat utilisation. The review highlights that future scenarios based on sustainable energy systems are viable, although their implementation will require further efforts by researchers and investors and active involvement of consumers. Highlights: Research trends on energy transition and the associated technologies are reviewed. Literature review examined the Special Issues of journals dedicated to SDEWES Conferences. Challenges posed by increased share of renewables are solvable by cost-efficient solutions. Power-to-heat and district heating are key-technologies for sustainable energy supply. Energy saving in the building and industrial sectors contributes to sustainability of energy sector.